2021
DOI: 10.3233/jad-210400
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor Targeting NLRP3 Inflammasome Reduces Neuropathology and Improves Cognitive Function in Alzheimer’s Disease Transgenic Mice

Abstract: Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, and the most common type of dementia. A growing body of evidence has implicated neuroinflammation as an essential player in the etiology of AD. Inflammasomes are intracellular multiprotein complexes and essential components of innate immunity in response to pathogen- and danger-associated molecular patterns. Among the known inflammasomes, the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome plays a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…The obtained data reasonably explains the emergence of cognitive and motor deficits in our model, as inflammation is associated with such elicited acute disturbances following TBI 63 66 . Sirtuin 1 (SIRT1) is also an essential element for normal cognitive function and synaptic plasticity 67 and proved to enhance cognitive dysfunction in many studies 68 , 69 . The measured SIRT1 levels were also suppressed post TBI 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The obtained data reasonably explains the emergence of cognitive and motor deficits in our model, as inflammation is associated with such elicited acute disturbances following TBI 63 66 . Sirtuin 1 (SIRT1) is also an essential element for normal cognitive function and synaptic plasticity 67 and proved to enhance cognitive dysfunction in many studies 68 , 69 . The measured SIRT1 levels were also suppressed post TBI 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Then, Chiu et al (2021) found that SG-Tang could act as a neuroprotective agent against Aβ aggregation and neuroinflammation by regulating the NLRP1/NLRP3 pathway. Subsequently, Kuwar et al (2021) suggested that loaded Aβ can be reduced significantly, alleviate neuroinflammation, improve hippocampal neuronal activity, and relieve cognitive function in APP/PS1 mice via inhibiting NLRP3 inflammasome with JC124. Even though limited studies have probed the role and underlying mechanism of NLRP3 inflammasome-mediated pyroptosis in AD, the mechanisms of how NLRP3 inflammasome drive pyroptosis need further study.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, fatty acid caused by a high-fat diet activates the NLRP3 inflammasome through the molecular axis AMPK–autophagy–NF-kB-ROS [ 7 ]. Moreover, Amyloid β, post-translational modifications of NLRP3, and non-canonical inflammasome activations have been reported as triggers for the NLRP3 inflammasome [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%